A flexural isostasy model for the Pleistocene evolution of the Barents Sea bathymetry - Zieba, Krzysztof Jan; Omosanya, Kamaldeen Olakunle; Knies, Jochen (Norwegian Journal of Geology, 2017)
Source at: http://doi.org/10.17850/njg97-1-01 The topographic relief of the Barents Sea was subjected to major changes during the past 1.5 million years mostly due to sediment redistribution driven by glacial activity. This paper addresses the problem of Pleistocene bathymetric evolution of the southern Barents Sea using a numerical modelling approach that considers the influence of regional isostasy on relief development. The model presented in this work shows that most of the bathymetric features were initiated prior to the first documented, shelf-edge glaciations at around 1.5 Ma. During the Early Pleistocene (Calabrian), the Barents Sea shelf was close to sea level with some areas elevated to about 300 m. Most of the shelf experienced up to 200 m topography reduction during the Early to Middle Pleistocene (1.5–0.7 Ma) facilitating bifurcation of the North Atlantic waters into the Barents Sea. Later during the Middle Pleistocene–Present (0.7–0.0 Ma) the relief deepened by 0 to 250 m. Our results demonstrate that the present-day topography of the southern Barents Sea is the consequence of glacial activity influenced by a regional isostatic component, which is the result of selective trough erosion and significant sediment deposition at the Barents Sea margins during the Pleistocene.